- d
*u*= (∂*u*/∂*x*)_{y,z}d*x*+ (∂*u*/∂*y*)_{x,z}d*y*+ (∂*u*/∂*z*)_{x,y}d*z* - d
*u*= D_{1}*f*(*x*,*y*,*z*) d*x*+ D_{2}*f*(*x*,*y*,*z*) d*y*+ D_{3}*f*(*x*,*y*,*z*) d*z* - D
_{1}*f*(*x*,*y*,*z*) = (∂*u*/∂*x*)_{y,z} - D
_{2}*f*(*x*,*y*,*z*) = (∂*u*/∂*y*)_{x,z} - D
_{3}*f*(*x*,*y*,*z*) = (∂*u*/∂*z*)_{x,y} - ∇
*f*(*x*,*y*,*z*) = ⟨D_{1}*f*(*x*,*y*,*z*), D_{2}*f*(*x*,*y*,*z*), D_{3}*f*(*x*,*y*,*z*)⟩ - d
*u*= ∇*f*(*x*,*y*,*z*) ⋅ ⟨d*x*, d*y*, d*z*⟩ - d
*u*|_{⟨dx,dy,dz⟩=v}= ∇f(*x*,*y*,*z*) ⋅**v**

Go back to the course homepage.

This web page was written between 2014 and 2016 by Toby Bartels, last edited on 2016 April 19. Toby reserves no legal rights to it.

The permanent URI of this web page
is
`http://tobybartels.name/MATH-2080/2016SP/gradient/`

.